Virulência de micro-organismos à Plutella xylostella (L.) (Lepidoptera: Plutellidae) e compatibilidade com inseticidas - Duarte, Rogério Teixeira [UNESP] (2015)
Diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is one of the main pest in Brassicaceae family with control based on the indiscriminate use of insecticides, which has provided an increase in the number of cases of resistant populations to different active ingredients. Biological control, by using of entomopathogenic microorganisms is an important tool for the management of this pest. However, the main obstacle in terms of efficiency and conservation of these microbial agents in the field is related to the compatibility with pesticides. The aim of the research was to analyze the susceptibility of P. xylostella to entomopathogenic microorganisms and evaluate the compatibility of the most virulent entomopathogens with insecticides registered for the control of pest complex in cabbage crop. Efficiency of 13 isolates of the entomopathogenic bacterium Bacillus thuringiensis was analyzed, in addition to isolates of the entomopathogenic fungi Beauveria bassiana, Metarhizium rileyi, Isaria fumosorosea, I. sinclairii and Lecanicillium muscarium by performing pathogenicity and virulence tests (LC50 and LT50) on second instar larvae of P. xylostella. The interaction between the isolates and active ingredients was made from the mixture of the insecticide in the culture medium, inoculated with an aliquot of the microorganism suspension after medium solidify, evaluated the number of spores / mL (B. thuringiensis), and the colony growth, the number and conidia viability (entomopathogenic fungi) after seven days the inoculation of these microorganisms. The isolates of B. thuringiensis HD-1, HD-4, HD-11, HD-73 and T-07were the most efficient in P. xylostella control, responsible for overall mortality, with LC50 ranging from 0.75 to 11.66 × 103 spores / mL and TL50 between 25.12 to 34.47 h. The isolates IBCB01, IBCB18, IBCB66 and IBCB87 of B. bassiana, LCMAP101 of M. rileyi and ARSEF7973 of I. sinclairii caused mortality between ...